Drawing on difference : art therapy with people who have learning difficulties - Rees, Mair, 1960- (Routledge, 1998)
Drawing on Difference reveals how art therapy can support and validate the emotional and mental health needs of people with learning difficulties. Case studies present work with adults and children with differing degrees of difficulty.
Keywords: People with mental disabilities -- Rehabilitation.; Art therapy.; People with mental disabilities -- Mental health.; Art Therapy; Persons with Intellectual Disabilities -- rehabilitation.; Personnes ayant une déficience intellectuelle -- Réadaptation.; Art-thérapie.; Personnes ayant une déficience intellectuelle -- Santé mentale.; art therapy.; PSYCHOLOGY -- Neuropsychology.; Art therapy; People with mental disabilities -- Mental health; People with mental disabilities -- Rehabilitation; Kunsttherapie; Lernstörung; Aufsatzsammlung